QUALITATIVE STUDY ON COMPENSATION AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE IN COMPANIES LITERATURE REVIEW STUDY - Shofi Eka Pratiwi; Dyah Eka Amelia dyah amell; Silvi Hamidah; Rizaldi Al Farisi; Riyan Sisiawan Putra (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
One of the keys to the success of a company lies in the presence of quality human resources, namely competent employees who are able to deliver optimal performance. To achieve good performance from employees, it is important for us to provide appropriate and adequate compensation. Compensation is a form of remuneration given by the company to employees, which can be in the form of material and non-material, used by employees to meet their living needs. This study aims to analyze the compensation system and its implications for employee performance in the company. With this qualitative approach, the research emphasizes the context of the problem being studied. The author uses a qualitative research method with a literature review journal. All references in this study are sourced from Google Scholar, Sinta, and other online media. The research results show that the provision of compensation has a positive impact on employees. Therefore, companies need to pay attention to the aspect of compensation for employees in order to maintain and improve their performance. This form of compensation can include both financial and non-financial aspects, such as wages, allowances, social insurance, incentives, and comfortable facilities.